2023
DOI: 10.1111/aogs.14629
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis gravidarum: Associations with personal and family history of nausea

Venla S. Lindström,
Linda M. Laitinen,
J. Miina A. Nurmi
et al.

Abstract: IntroductionThe pathogenesis and risk factors for hyperemesis gravidarum, excessive nausea and vomiting of pregnancy, are not adequately recognized. In our previous study, we found that women with a personal history of nausea in different situations and a family history of nausea and vomiting of pregnancy (NVP) were more likely to have severe NVP. The present study focuses on these themes in association with hyperemesis gravidarum in a hospital setting.Material and methodsWomen with hyperemesis gravidarum (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In line with the literature, the results of our study showed a higher BMI, higher gravidity and higher parity in patients who did not have NVP. Higher BMI is associated with lower NVP rates, and since previous NVP is a signi cant risk factor for recurrence of NVP, it is not surprising that women who have experienced NVP and HG are less likely to want to become pregnant again [39,40]. Main ndings of the present study were: (1) SII and PIV were signi cantly higher in the NVP group than in the control group.…”
Section: Discussionmentioning
confidence: 50%
“…In line with the literature, the results of our study showed a higher BMI, higher gravidity and higher parity in patients who did not have NVP. Higher BMI is associated with lower NVP rates, and since previous NVP is a signi cant risk factor for recurrence of NVP, it is not surprising that women who have experienced NVP and HG are less likely to want to become pregnant again [39,40]. Main ndings of the present study were: (1) SII and PIV were signi cantly higher in the NVP group than in the control group.…”
Section: Discussionmentioning
confidence: 50%
“…13 A recent study found that participants with a personal history of motion sickness and nausea associated with migraine were at increased risk for hyperemesis gravidarum. 14 In addition, a nationwide study in the United Kingdom of more than 8 million pregnancies demonstrated that certain comorbid medical conditions, such as type 1 diabetes mellitus, thyroid dysfunction, and hypercholesterolemia, are associated with hyperemesis gravidarum. 15…”
Section: Epidemiology Risk Factors and Clinical Morbiditiesmentioning
confidence: 99%
“…Immediate goals of inpatient treatment are stabilization through rehydration and electrolyte repletion. 11 3.2 (1.6-6.4) Nulliparity 15 0.9 (0.89-0.91) for parity 1 or more Young maternal age 70 1.94 (1.77-2.12) for age younger than 20 y; 1.44 (1.38-1.52) for age 21-25 y Female fetus 15 1.23 (1.22-1.25) Multiple gestation 15 2.41 (2.24-2.59) Personal history of motion sickness 14 5.24 (2.67-10.31) Maternal comorbid medical conditions Parathyroid dysfunction 15 3.83 (2.28-6.44) Thyroid disorders 15 1.85 (1.74-1.96) Type 1 diabetes 15 1.95 (1.82-2.09) Hypercholesterolemia 15 2.54 (1.88-3.44) Helicobacter pylori infection 71 3.32 (2.25-4.90) Migraine headaches with nausea 14 3.00 (1.58-5.70) Use of ART 70 2.19 (1.81-2.64) BMI 72 2.36 (1.43-3.88) for underweight; 1.48 (1.00-2.20) for overweight…”
Section: Inpatient Managementmentioning
confidence: 99%